2004
DOI: 10.1089/153623104773547471
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoMetabolic Model and Protein Expression ofHaemophilus influenzaeStrain Rd KW20 in Rich Medium

Abstract: The intermediary metabolism of Haemophilus influenzae strain Rd KW20 was studied by a combination of protein expression analysis using a recently developed direct proteomics approach, mutational analysis, and mathematical modeling. Special emphasis was placed on carbon utilization, sugar fermentation, TCA cycle, and electron transport of H. influenzae cells grown microaerobically and anaerobically in a rich medium. The data indicate that several H. influenzae metabolic proteins similar to Escherichia coli prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 54 publications
3
46
1
3
Order By: Relevance
“…This trend was unchanged for the 10 H.in¯uenzae genes that did not have E.coli orthologs. These data and the apparent discrepancies in gene essentiality between H.in¯uenzae and E.coli (Table 1S) reiterate the fact that the H.in¯uenzae genome is not just a subset of E.coli genes (34,35).…”
Section: Identi®cation Of`hypothetical' Genes Expressed In Hin¯uenzaementioning
confidence: 58%
See 1 more Smart Citation
“…This trend was unchanged for the 10 H.in¯uenzae genes that did not have E.coli orthologs. These data and the apparent discrepancies in gene essentiality between H.in¯uenzae and E.coli (Table 1S) reiterate the fact that the H.in¯uenzae genome is not just a subset of E.coli genes (34,35).…”
Section: Identi®cation Of`hypothetical' Genes Expressed In Hin¯uenzaementioning
confidence: 58%
“…Gene and protein expression studies of the cells grown under normal or stressed conditions can help determine when (if ever) these genes are expressed and sometimes suggest their functions. A major bottleneck of such studies is the reliability of the data, which has to be ensured through rigorous statistical analysis (11,35,53,56).…”
Section: Discussionmentioning
confidence: 99%
“…The mucosa of the nasopharyngeal region and the upper respiratory and genital tracts are the niches which can be occupied by most Pasteurellaceae species in mammals, and when the commensal state inadvertently leads to disease, these species are also able to enter the bloodstream and the cerebrospinal fluid. It is suggested that such niches may provide microaerophilic conditions and, as deduced from the gene content of H. influenzae, the metabolism of these organisms seems to be more oriented toward reductive than oxidative conditions (69). The host compartments compensate for the bacterial NAD ϩ auxotrophy and contain NAD ϩ or related intermediates in concentrations appropriate for the survival and growth of bacteria.…”
Section: Making It Small: the Nad ؉ Pathway Of The Pasteurellaceaementioning
confidence: 99%
“…1 Over the past ten years, genome-scale stoichiometric metabolic models have been built for a variety of organisms, including E. coli, S. cereviseae, H. pylori, S. aureus, and H. sapiens. [2][3][4][5][6][7][8][9][10][11][12][13][14] Such models facilitate analysis of systems-level behaviors such as growth or metabolite production in the context of nutrient media and chemical/genetic perturbations. 14,15 Part of the complexity of metabolism arises from the existence of backup pathways for a given function.…”
Section: Introductionmentioning
confidence: 99%